Smash the dichotomy of Skeuomorphism and flat design: Designing an affordable interface to correspond with the human perceptuomotor process. Issue 141 (September 2020) - Kim, Sangyeon; Lee, Sangwon
Highlights: Skeuomorphism and flat design are not different to afford a user's actions at the perceptuomotor level. The design styles are muddled with dimensionality and visual metaphor. Visuo-perceptual familiarity is more critical to afford a user's actions than dimensionality. A design physically compatible with user manipulation is more important for affording a user's actions than a real-world metaphor. Using a conventional metaphor as a signifier can increase a user's ability to perceive how they can interact with interfaces. Abstract: Skeuomorphism and flat design, which are the most prevalent design styles, have both striven for supremacy in interface design. A consensus has not been reached due to inconsistent findings in academia and groundless arguments on the internet. In this article, we aim to explore perceptuomotor differences between these two design styles via object-based correspondence effects. Experiments with object-based correspondence effects allow the affordance to be measured quantitatively, comparing both perceptual and operational aspects of each design style. In Experiment 1, the two design styles are compared in terms of the correspondence effect between handle-orientation (left/right) and a user's responding hand (right hand/left hand). In Experiment 2, the two design styles are compared in terms of the correspondence effect between object size (big/small) and grip type (power grip/precision grip). The results in both experiments indicate that the two design styles are not different at the perceptuomotor level. This demonstrates that an affordance is similarly evoked in digital objects designed with either skeuomorphism or flat design. Further, we discuss the reason for the inconsistent findings in previous research, concluding that results have been influenced by unfamiliar forms and inappropriate real-world metaphors. Based on the conclusions, we suggest three design principles that designers can use to avoid confusion related to the design styles. In our discussion, we determine that the design styles are muddled with dimensionality and metaphor, which increases the inconsistent research findings in the literature. Finally, we suggest that the dichotomy between skeuomorphism and flat design is discarded.